Optimalisasi Penjualan Melalui Peningkatan Kualitas Packaging Produk Dalam Pengembangan UMKM Di Desa Cerme, Kec. Juwangi, Kab. Boyolali - Endang Dwi W; Hani Krisnawati; Dimas Adi Wicaksono; Kasidi Kasidi; M. Anik Mashadi; Yunior Arjuna (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Micro, Small, and Medium Enterprises (MSME) development strategies, namely through training and mentoring will help MSMEs manage their business more effectively, increasing market access through e-commerce platforms,effective marketing strategies, and collaboration with distributors and retailers will help MSMEs to expand market share and increase sales, as well as collaboration between MSMEs and empowerment of local business networks. Increasing market access through e-commerce platforms,effective marketing strategies, and collaboration with distributors are important strategies for MSMEs in expanding product reach and increasing sales, such as online marketplaces, so that MSMEs can reach consumers in various locations without being limited by geographic boundaries, use of media social, creative product promotion, and selecting the right market segment and collaborating with distributors and retailers.